Competition Policy and Economic Reform Conference: Donald J. Johnston - CADE, Conselho Administrativo De Defesa Econômica (Revista do IBRAC, 2025)
Mr. President, On behalf of the Organisation for Economic Co-operation and Development, I would like to thank you for your personal support for this important conference on Competition Policy and Economic Reform, which opens today. Not being able to attend, I should like to convey to you my personal wishes for the success of this meeting which I sincerely hope will constitute a landmark for competition policy and economic reform more generally in your country and in Latin America.